Waste material flow analysis in the Łódź Metropolitan Area - Czapiewski, Konrad; Mazurek, Damian; Traczyk, Anna; Wójcik, Marcin (European Spatial Research and Policy, 2020)
The main sources of waste generation are: industry, municipal sector, and agriculture. Municipal waste is solid and liquid waste that arise in households, public utilities (trade, services, handicrafts) and municipal services (e.g. street cleaning and maintenance of green areas). The main aim of this paper are the analysis of the flow of municipal solid waste in Łódź Metropolitan Area, its composition, presentation of the process towards a more selective waste system, and the extraction of biodegradable waste from the MSW. The article is based on a report prepared within the Horizon 2020 project REPAiR “Resource Management in Peri-urban Areas: Going Beyond Urban Metabolism”.